PENERAPAN METODE PEMBELAJARAN ACTIVE LEARNING MENGGUNAKAN MODEL PERMAINAN KARTU DALAM MENINGKATKAN MOTIVASI BELAJAR PKN SISWI SMAN 1 CIKARANG UTARA - Andri Cahyo Purnomo; Astri Russy Rachmani (Al-Fikru : Jurnal Pendidikan Dan Sains, 2022)
This study aims to improve the motivation to learn Civics using active learning method. This research was conducted in class X.5 which amounted to 34 students. The method used in this research is classroom action research method (PTK) which carried out as many as three cycles. In the first cycle directly using the active learning method with the card game model in learning Civics, because it was noticed at the beginning of observation that the study of learning class X.5 is still low, after using the method of active learning student motivation questionnaire as much as 57.64%. In the second cycle of learning motivation has increased, this can be seen from the increase of students' learning motivation, the spirit of competing in a healthy, active in answering questions and asks, cooperation among students and the increase of questionnaire results of student learning motivation in the second cycle as much as 71.76%. Civic learning activities in the third cycle by using the card game model can improve student learning motivation, this can be seen from the result of questionnaire student learning motivation as much as 76.03%. The results of the study increase the learning motivation from the first cycle to the second cycle of 14.12%, from the second cycle to the third cycle increased by 4.27%, so the increase in learning motivation from cycle one to third cycle increased by 18.39%. Based on the results of research that has been done, it can be concluded that the application of active learning method of card game can improve student learning motivation in Civics subjects in class X.5 in Senior High School 1 North Cikarang. Keywords: Active learning Method, Card Game Model, Learning Motivation